Respuesta :

                 |2x - 1| + 3 = |-x + 5|
               ±(2x - 1) + 3 = ±(-x + 5)
(2x - 1) + 3 = -x + 5    or    -(2x - 1) + 3 = (-x + 5)
  2x - 1 + 3 = -x + 5             -2x + 1 + 3 = -x + 5
      2x + 2 = -x + 5                  -2x + 4 = -x + 5
     + x         + x                      + 2x      + 2x
      3x + 2 = 5                                 4 = x + 5
            - 2  - 2                              - 5        - 5
             3x = 3                                -1 = x
              3     3
                x = 1